Fractography analysis of 1.0 wt% nanoclay/multi-layer graphene reinforced epoxy nanocomposites. (September 2017) - Atif, Rasheed; Inam, Fawad
The topographical features of fractured tensile, flexural, K1C, and impact specimens of 1.0 wt% multi-layered graphene/nanoclay-epoxy nanocomposites have been investigated. The topographical features studied include maximum roughness height ( R max or R z ), root mean square value ( R q ), roughness average ( R a ), and waviness ( W a ). Due to deflection and bifurcation of the cracks by nanofillers, specific fracture patterns are observed. Although these fracture patterns seem aesthetically appealing, however, if delved deeper, they can further be used to estimate the influence of nanofiller on the mechanical properties. By a meticulous examination of topographical features of fractured patterns, various important aspects related to fillers can be approximated such as dispersion state, interfacial interactions, presence of agglomerates, and overall influence of the incorporation of filler on the mechanical properties of nanocomposites. In addition, treating the nanocomposites with surfaces of specific topography can help improve the mechanical properties of nanocomposites.